Surface functionality analysis by Boehm titration of graphene nanoplatelets functionalized via a solvent-free cycloaddition reaction. Issue 4 (30th January 2019) - Ren, He; Cunha, Eunice; Sun, Quanji; Li, Zheling; Kinloch, Ian A.; Young, Robert J.; Fan, Zhaodong
Abstract : Carboxylic acid-terminated pyrrolidine functionalities were covalently bonded to the surface of graphene nanoplatelets via a solvent-free approach and characterized by Boehm titration. Abstract : In this work, the functionalization of graphene nanoplatelets (GNPs) performed by a solvent-free cycloaddition reaction on GNPs with iminodiacetic acid (IDA) and paraformaldehyde (PFA), and the functionality analysis of the resulting functionalized GNPs (f-GNPs) by Boehm titration are introduced. The f-GNPs synthesized at different temperatures were characterized by X-ray diffraction (XRD), Raman spectroscopy and scanning electron microscopy (SEM) for structural and morphological properties. Back titration of the f-GNPs selectively identified 3 types of functional groups on the f-GNP surface, carboxylic, lactonic and phenolic, and suggested that 200 °C gives the highest carboxylic group functionality. With the reaction temperature increasing from 180 to 220 °C, a decrease in the phenolic functionality and an increase in that of lactonic are observed. In the case of 250 °C reactions, it was found that the carboxylic functionality is greatly reduced, while the phenolic functionality showed a significant increase. The f-GNP samples were further characterized by thermogravimetric analysis (TGA) and X-ray photoelectron spectroscopy (XPS), the results of which showed a good agreement with the titration analysis.